Limited Equity Cooperative Housing: An Alternative to Cope with The Lameness of Urban Land Ownership - Eisenring, Tommy S. S. (Journal of Regional and City Planning, 2008)
This article is intended to discuss the lameness of land ownership system in our cities, and to describe the idea to cope with the lamness through the application of a program for the provision of homesteading, i.e. ‘Limited Equity Cooperative Housing’ using a system approach. The discussion is begun with some theoretical views capable of explaining urban poverty in the  Third  World,  i.e.  Marginai  theory,  Developmental  theory,  Dependency  theory  and  Articulatory theory. These theoretical views become the bases for the discussion on finding policies to cope with the land system in our cities which causes the impecunious group of urban people which has high proximity level to the urban activities center, cannot obtain affordable housing. The discussion began with the description about the concept of Limited Equity Cooperative Housing as an alternative. Then, discussion regarding a system approach to applying a program for the provision of homesteading through the combination of “button:-up” and “top- down” model. The discussion ends with the description of basic strategy  to  implement  the  program  by  using  General  Action  System  model  introduced  by  Taicoot Parsons. Finaly, this article ends with policy implication and conciusion.